Reconciling Maṣlaḥah and the Rule of Distinction in the Yemen Conflict - AL-Dafrawi, Ahmad Saad Ahmad; Yahya, Muhammad Tahir (Prophetic Law Review, 2025)
The prevailing discourse on armed conflict frequently asserts that the difficulty in safeguarding civilians does not arise from an absence of legal norms. Instead, it reflects the persistent failure of both state and non-state actors to comply with existing regulations, particularly those embedded in International Humanitarian Law (IHL). A closer examination, however, reveals that such non-compliance is often enabled by the strategic exploitation of ambiguities and structural weaknesses within the legal framework itself, regardless of the normative authority or humanitarian values these laws embody. The effectiveness of civilian-protection regimes therefore depends not only on the existence of legal provisions but also on their robust promotion, contextual legitimation, and implementation mechanisms that meaningfully engage and protect the intended beneficiaries. Against this backdrop, the present study conducts an in-depth exploration of the intersection between al-Maṣlaḥah (public interest) and the IHL principle of distinction within the specific context of Yemen’s protracted armed conflict. By adopting a case-study design supported by qualitative analysis of conflict documentation and reports, the research investigates how the synergy between al-Maṣlaḥah and the principle of distinction might inform more responsive and culturally grounded strategies to enhance civilian protection and reduce harm in complex and asymmetrical warfare settings. Drawing on Islamic jurisprudential thought, foundational IHL doctrines, and empirical evidence from Yemen, the study offers nuanced insights into both the structural challenges and latent opportunities for strengthening civilian-protection frameworks. Ultimately, it seeks to contribute to a more integrative and context-sensitive approach to civilian protection in contemporary armed conflicts.